Interpreting Modernity in Culturally Pluralized Cities. (2016) - Dev, Animesh
Abstract: Socio-cultural Unity in diversity is an Aesthetic symbol of man's collective agglomerations. In urban grouping and majorly due to economics, divisions dissolve and people naturally come together. A city is more than a place in space, it is a drama in time, (Patrick giddies, 1910) and bridge divides between groups of people. Sometimes, which is becoming more common as time passes, the agglomeration of cultures at the point called city is not a celebratory moment. It comes with social stiffness among aboriginals, co-migrants and immigrants. Also, the aspirations dissolve in unsustainable physical conditions of living in the mega habitats of developing and underdeveloped countries. A successful multicultural environment is one where various cultural set's sense of comfort is combined with good physical design and addressing intangible attributes to create an atmosphere that can nurture many individual and communal preferences; a place that fosters social interaction while simultaneously creating distinct spaces where individual cultures can be acknowledged and celebrated. [1] Our future cities shall be the urban places of aspirations where men by mutual society complement each other, do grow to social alliances, multiplicities in commonalities, and existential corporations. [2]